PEMBERDAYAAN WARGA DALAM PENANGGULANGAN KEBAKARAN DI KECAMATAN SERPONG UTARA KOTA TANGERANG SELATAN - Jukri, Jukri; Inneka, Tito (Universitas Muhammadiyah Tangerang, 2023)
A fire-free urban community environment can be created through early fire prevention and suppression efforts. This early fire prevention and suppression aims to develop community-based fire preparedness. The forms of fire prevention efforts carried out by the community include simulations, counselling, and training on fire hazards, as well as being a member of the Fire Volunteer Front. It is hoped that this model will be more easily accepted by the public because it is part of the South Tangerang City Fire and Rescue Service program.